2010
DOI: 10.1186/1756-0500-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs change their expression profile after Retinoid induced differentiation of the promyelocytic cell line NB4

Abstract: BackgroundThe importance of non-coding RNAs (ncRNAs) as fine regulators of eukaryotic gene expression has emerged by several studies focusing on microRNAs (miRNAs). miRNAs represent a newly discovered family of non coding-RNAs. They are thought to be crucial players of human hematopoiesis and related tumorigenesis and to represent a potential tool to detect the early stages of cancer. More recently, the expression regulation of numerous long ncRNAs has been linked to cell growth, differentiation and cancer alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In addition to micro RNAs (miRNAs) being regulated by atRA1314, several lncRNAs have been reported to be influenced by atRA in neuronal and cancer cells. In rats, atRA is involved in hippocampal functions by up-regulating LINC_RBE15 and is able to restore NEAT1 expression in NB4 leukemia cell differentiation16.…”
Section: Ncrnas and Atramentioning
confidence: 99%
“…In addition to micro RNAs (miRNAs) being regulated by atRA1314, several lncRNAs have been reported to be influenced by atRA in neuronal and cancer cells. In rats, atRA is involved in hippocampal functions by up-regulating LINC_RBE15 and is able to restore NEAT1 expression in NB4 leukemia cell differentiation16.…”
Section: Ncrnas and Atramentioning
confidence: 99%
“…In APL cells, RA upregulated the expression of miR-186, miR-215 and miR-223 , while it downregulated the expression of miR-17, miR-25, miR-193, miR-195 [29]. In another study using the same cells, RA was found to upregulate the expression of miR-15a, miR-15b, miR-16-1, let-7a-3, let-7c, let-7d, miR-107, miR-223, and miR-342 , whereas miR-181b was downregulated [30].…”
Section: Modulation Of Mirna Expression By Natural Agentsmentioning
confidence: 99%
“…Furthermore, the recruitment of NF-kB on the let-7a-3/let-7b cluster promoter upon treatment with retinoic acid suggests that this is the mechanism of regulation of miRNA expression in this case (125) . Conversely, authors of a later study of ATRA differentiation in NB4 cells reported that let-7a was down-regulated following ATRA treatment (126) . This apparent contradiction is probably due to the differences in culture time used in the two experiments (48 h (125) , compared with 6 d (126) ).…”
Section: Retinoic Acidmentioning
confidence: 99%
“…Conversely, authors of a later study of ATRA differentiation in NB4 cells reported that let-7a was down-regulated following ATRA treatment (126) . This apparent contradiction is probably due to the differences in culture time used in the two experiments (48 h (125) , compared with 6 d (126) ). This highlights the importance of the temporal specificity of the relationships between nutrients, miRNA expression and physiological consequences and this needs to be considered in furthering these studies.…”
Section: Retinoic Acidmentioning
confidence: 99%